Antioxidative Activity and Phenols Content in Five Tropical Lamiaceae Plants (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
The total antioxidants content in five Lamiaceae plants were examined. Fresh Plecranthus amboinicus Lour. Indonesia leaves were collected from Jakarta, Indonesia and leaves of Plecranthus amboinicus Lour. Malaysia, Pogostemon cablin Benth., Solenostemon scutellariodes Red and Solenostemon scutellariodes Mix Colour were collected from Kuantan, Malaysia. Leaves were freeze-dried, ground and extracted using methanol. The extracted leaves were determined the scavenging activity of the stable 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay. Results showed that the P. cablin Benth. leaves exhibited the significant (p
Keywords: Scavenging activity; Antioxidants; Plecranthus amboinicus; Pogostemon cablin; Solenostemon scutellaroides; Phenolics